(3TQM eYGde CUhd GdOjfs - (3TQa GdOjf CHh eMeO YHO Gddg Hf eMeO Hf Ydj GdeYQha HGHf GdJdeSGfis; (3aNQ GdOjf eMeO Hf GdNWjHs
(3ChdgG (B:s
(3gPG JYdjb LeYJg Ydi eYGde CUhd GdOjf ddEeGe aNQ GdOjf eMeO Hf GdNWjH bhdg agPG eNJUQ eTJed Ydi CfhGY ef GdYdhe GdegeI s
(3BNQgG (B:s
(3hLhH GdYUeI TQW dUMI GdCeGfI hbGd GdHGbhi Gfg djS dPdc dfG Ci GdOdjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdeLGejYs